Health Literacy questionnaire development for 9 and 10 years old: a discussion of assessment tools!. (13th November 2019) - Reis, A; Barroso, I; Saboga-Nunes, L; Okan, O; Bollweg, T; Bittlingmayer, U
Abstract: Background: With Health literacy (HL) investments - to promote health and self-care during people's life cycles (childhood, especially) - health professionals approach is multi-dimensional: within the family, school settings and community. The objective of this study is to explore the feasibility and usability of a questionnaire to characterize HL levels among 9 and 10 years old. It is expected that this will help health care personal to better focus health promotion initiatives in the school setting. Methods: The CrAdLiSa project in conjunction with the HLCA German Consortium, implemented a field test for the newly developed HL assessment tool for children in the Portuguese context. This is a deductive-inductive, exploratory-descriptive study including 16 children, with 9 and 10 years old, from 2 different elementary schools in Santarém District (rural and urban areas). Semi-structured interviews aim at exploring the cognitive appraisal of concepts and indicators at the base of the questionnaire developed to assess HL levels. Data was subjected to content analysis, with a priori and a posteriori categorization. Results: Preliminary results point to the cognitive comprehension by children of the feasibility of an instrument to assess their HL levels. It depicts discriminatory capabilities (to allow characterization of low, medium or high levels of HL). Children living in urban areas, having better financial resources are less likely to develop obesity, or low weight. Better self-perception of school performance, good relationship with family members, parents with higher education or higher levels of HL appear to have better quality of life. Conclusions: Results suggest the need to invest in children's and families' HL, while taking into consideration personal, environmental and socioeconomic determinants. School settings should be considered as a natural arena to improve children's (and, as a result, families' and communities') HL levels.